EDITORIAL - Vongurai, Rawin (Scholar: Human Sciences, 2023)
The Scholar: Human Sciences, a journal encompassing the fields of humanities and social sciences, has earned acclaim in the Thailand Citation Index (TCI) as a prominent publication since 2015. It currently holds the esteemed TCI: TIER2 classification. We take great pride in presenting the latest issue, Scholar: Human Sciences Vol. 15 No. 2 (July – December 2023), which features a collection of manuscripts that have undergone rigorous evaluation. Each submission has been meticulously reviewed through a blinded review process by three specialized reviewers from different institutions, both internal and external to the authors. This peer-reviewed accreditation ensures the scholarly quality and integrity of the published articles. This issue covers twenty-six articles. The first article titled “Drivers of Behavioral Intention to Adopt Hybrid Education of Undergraduates in Arts and Design’s in Chengdu, China” aims to determine drivers of behavioral intention to use hybrid education of undergraduate students in Arts and Design in three universities in Chengdu, China. The second article titled “Attitude Towards Use and Behavior Intention of Online Art Appreciation Courses in Public Universities in Yunnan, China” aims to develop a model to predict the key factors affecting the behavior intention to adopt online art appreciation courses of undergraduate students. The third article titled “Undergraduates’ Behavioral Intention to Use E-Guests to Facilitate Online Learning in The Public Universities in Chongqing, China” aims to evaluate the determinants that significantly affect undergraduate design students’ behavioral intentions to invite e-guests in online education from three essential public universities in Chongqing, China. The fourth article titled “Behavioral Intention to Use E-learning: A Case Study of Apparel School Students at Chengdu Textile College in China” aims to study significant factors of school of apparel students’ behavioral intention to utilize e-learning at Chengdu Textile College, including perceived ease of use, perceived usefulness, attitude, self-efficacy, performance expectancy, social influence and behavioral intention. The fifth articled titled “Factors Impacting Customer Loyalty of Online Shopping: A Case Study of China’s E-Commerce Platforms” aims to investigate the factors impacting satisfaction, commitment, and customer loyalty of online shopping. The sixth article titled “Behavioral Intention to Use Mobile Reading Apps Among Female Students in Chengdu, China” aims to analyze the factors affecting behavioral intentions of female students in Chengdu, China, to use and purchase mobile reading applications. The seventh article titled “Factors Affecting Students’ Continuous Intention to Use Online Art Education Software in Chengdu, China” explores the analysis of factors influencing the continuous use of online art education software by private art education institutions in Chengdu, Sichuan Province, China. The eighth article titled “French Horn Students’ Performance Improvement and Perceptions of Learning through Synchronous Virtual Classroom: An Empirical Research at Hunan Normal University” aims to use a synchronous virtual classroom course to assess the sample participants’ performance improvement and perceptions; and then to analyze and evaluate the results from the assessment. The ninth article titled “Influential Factors of Travel Bubbles Intention During COVID-19 among Cambodians in Siem Reap and Preah Sihanouk” aims to examine the influential factors of travel bubbles intention during COVID-19 among Cambodians in Siem Reap and Preah Sihanouk. The tenth article titled “The Improvement of Service Quality of Service Quality in Prefabricated Steel Structure Construction Process” aims to investigate customers’ perceptions of service quality and present guidelines for improving services in prefabricated steel structure management. The eleventh article titled “The Assessment on Consumer Satisfaction and Use Intention of B2C E-Commerce Platform in Chongqing, China” assesses the factors affecting the satisfaction and use intention of Chongqing residents toward e-commerce platforms, including service quality, information quality, system quality, perception of ease of use, perception of usefulness, intention, and satisfaction. The twelfth article titled “The Determinants of Behavioral Intention to Use Mobile Reading Apps of Collage Students in Chongqing, China” aims to examine the determinants of behavioral intention of college students in Chongqing who have mobile reading experience of excellent Chinese traditional culture. The thirteenth article titled “An Examination on Online Learning Adoption of Postgraduate Students in Chengdu, China During COVID-19” aims to examine the online learning adoption of college students in Chengdu, China. Technology acceptance model (TAM) and the unified theory of acceptance and use of technology (UTAUT) incorporates perceived ease of use, perceived usefulness, attitude, social influence, facilitating conditions, behavioral intention, and use behavior. The fourteenth article titled “Investigating Continuance Intention to Use E-Learning of Female Students Majoring in Music in Chengdu” aims to investigate the impact of system quality, subjective norms, interactivity, course content quality, perceived usefulness, and satisfaction on the continuance intention to use e-learning of music major college students in Chengdu, China. The fifteenth article titled “Determinants of Patients’ Behavioral Intention and Loyalty in Private Hospitals in Chengdu, China” aims to investigate the causal relationship between medical cost reasonableness, healthcare technicality, interpersonal behavior, service quality, patient satisfaction, behavioral intention, and patient loyalty. The sixteenth article titled “The Determinants of Behavior Intentions to Use Chinese Animation and Comics Platforms of Senior Students in Chengdu, China” investigates the determinants of behavioral intentions to use Chinese animation and comics platforms of senior students in Chengdu, China. The seventeenth article titled “An investigation on Senior Students’ Behavioral Intention to Use Tencent Meeting for Legal Course in Chengdu, China” examines senior students’ behavioral intention to use Tencent meeting for the legal course in Chengdu, China. The eighteenth article titled “Determinants Influencing Middel School Students’ Loyalty to Intangible Cultural Heritage in Mianyang, China ” aims to evaluate the essential determinants that significantly impact students’ loyalty to intangible cultural heritage art practice courses in three secondary schools in Mianyang, China. The nineteenth article titled “Measuring First-Year Students’ Behavioral Intention and Use Behavior of Chaoxi Online Learning Platform to Study Mental Health Course in Chengdu, China” aims to measure first-year students’ behavioral intention to use Chaoxi online learning platform to study mental health courses in Chengdu, China. The twentieth article titled “Determinants of Taxpayers’ Use Behavior of Cambodia Road Tax Mobile Payment in Siem Reap” examines determinants of taxpayers’ use behavior of Cambodia Road Tax Mobile Payment Application (CRTMPA) in Siem Reap. The twenty-first article titled “English for Tour Operators and Tour Guides: Learning Needs from Stakeholders’ Voices” aims investigate learners’ needs through a survey to develop a course English for Tour Operators and Tour Guides as tourism has been one of the fastest-growing industries in the 21st century. The twenty-second article titled “Purchase Intention of Potential Hypertension Patients on Innovative Personal Health Assistant Services: A Case of a Private Hospital in Bangkok” aims to examine the significant impact of brand image, perceived service quality, patient satisfaction, and word of mouth on purchase intention on innovative personal health assistant services of patients with the potential to have hypertension. The twenty-third article titled “Influential Factors of Usage Behavior of Potential Hypertension Patients to Use Personal Health Assistant Service and Technology in a Private Hospital in Bangkok” aims to investigate the determinants of behavioral intention toward using personal health assistant services and technology for potential hypertension patients in a private hospital in Bangkok. The twenty-fourth article titled “Analysis of Undergraduate Students’ Behavioral Intentions and Usage Behavior of Online Learning Platforms in Chengdu, Sichuan, China” examines the factors affecting behavioral intention and usage behavior of online learning platforms among undergraduate students in Xihua University in Chengdu, Sichuan, China. The twenty-fifth article titled “The Influence of Service Quality Aspects on Satisfaction and Loyalty of Graduate Students in Chongqing, China” aims to determine the significant effect of faculty services, campus infrastructure, academic aspects, university reputation, and access to university services to determine student satisfaction and student loyalty. The twenty-sixth article titled “Determinants of Satisfaction and Continuance Intention to Use Cloud-Based E-Learning Among Undergraduate Students in Ningxia Universities” examines what factors affect the satisfaction and continuance intention of college students majoring in English translation and interpreting on cloud-based e-learning.